Comparative analysis of the changes in blood chemistry among long-distance swimmers during workouts at middle and low altitudes - Bakayev, V.; Bolotin, A.; Surmilo, S.; Aganov, S. (World Congress of Performance Analysis of Sport XII, 2018)
The paper describes differences between the responses of the body to training load among stayer athletes preparing for swimming competitions at middle or low altitude. This was reflected in the extent of biochemical factors of blood` alterations. During the studies both groups of sportsmen demonstrated the same dynamic of change in blood biochemical factors. There was a slight initial decrease in the majority of blood values (leukocytes, hemoglobin, erythrocytes, neutrophils) with further increase up to the starting point. However, among long-distance swimmers of the treatment group, trained at middle altitudes, showed a higher range of blood value fluctuations. It was found, that they recover faster after training load than the swimmers, trained at low altitudes. It reflects the fact, that a post-workout recovery speed depends on a range of blood chemistry fluctuations.